2017
DOI: 10.1111/ajo.12656
|View full text |Cite
|
Sign up to set email alerts
|

Views of the obstetric profession on non‐invasive prenatal testing in Aotearoa New Zealand: A national survey

Abstract: There was strong support for public funding of NIPT, and for NIPT capability to be developed in NZ. The call for more training, education and support needs to be actioned in order to facilitate the introduction of NIPT into screening services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Our survey response rate was 30.7%. This compares favourably to previously published surveys of healthcare professionals, which have response rates varying from 15.9 to 36.5% [9,[15][16][17], but may limit the generalizability of the results. Non-specialists and consultants practising in public hospitals were also overrepresented.…”
Section: Limitationssupporting
confidence: 65%
See 1 more Smart Citation
“…Our survey response rate was 30.7%. This compares favourably to previously published surveys of healthcare professionals, which have response rates varying from 15.9 to 36.5% [9,[15][16][17], but may limit the generalizability of the results. Non-specialists and consultants practising in public hospitals were also overrepresented.…”
Section: Limitationssupporting
confidence: 65%
“…Median total confidence scores were higher among MFM specialists (19/20, 95% CI 18-19.29) versus non-MFM specialists (17/20, 95% CI [16][17], and specialists felt more confident providing pre and post-test counselling (18/20, 95% CI 17.7-19) than non-specialists (16/20, 95% CI 15-16.1).…”
Section: Confidence In Providing Pre and Post-test Counsellingmentioning
confidence: 98%
“…Time mentioned above counted the consultation time by physicians only, and not the nurse-counseling time. One national survey reported that 45.8% of respondents answered that about 15 minutes is appropriate amount of time for pretest counseling [14]. Our survey shows that amount of time for pretest counseling by physician was shorter compared to above ideal time.…”
Section: Discussionmentioning
confidence: 59%
“…However, 31% would offer this, despite recognising a strong son preference, with participants suggesting the illegal status of abortion for social reasons in Pakistan as sufficient protection against sex‐selective TOP . A 2017 survey of obstetric professionals in New Zealand found that 37% had been asked about using NIPT for sex determination, and 33% supported the public funding of NIPT sex determination …”
Section: Nipt Sex Determination and Sex Selectionmentioning
confidence: 99%